(untitled) (American Journal of Islam and Society, 1991)
Translation In the name of Allah, Most Gracious, Most Mercifil. 1. Nay, but [Allah is aware of] those who keep their bond with Him, and are conscious of Him: and, verily, Allah loves those who are conscious of Him. Al ‘Imran (3:76) 2. And spend [freely] in Allah’s cause, and let not your own hands throw you into destruction; and persevere in doing good: behold, Allah loves the doers of good. Al Baqarah (2:995) 3. And how many a prophet has had to fight [in Allah’s cause], followed by many Allah-devoted men: and they did not become faint of heart for all that they had to suffer in Allah’s cause, and neither did they weaken, nor did they abase themselves [before the enemy], since Allah loves those who are patient in adversity. Al ‘Imran (3:146) 4. And it was by Allah’s grace that thou [O Prophet] didst deal gently with thy followers: for if thou hadst been harsh and hard of heart, they would indeed have broken away from thee. Pardon them, then, and pray that they be forgiven ...